Issues at the Rural-Urban Fringe: Florida State Laws Related to Land Use - Rodney L. Clouser; Michael T. Olexa (EDIS)
EDIS fact sheet FE549 (Issues at the Rural-Urban Fringe: Land Use Conflicts), addressed three broad categories of conflicts: noise, odor, and related issues; infrastructure concerns; and property rights and wealth distribution issues. This fact sheet is a companion commentary that specifically reviews state laws passed in Florida directly or indirectly related to land use on the rural urban fringe. This is EDIS document FE550, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. This document is one of a series entitled "Issues at the Rural Urban Fringe". Published May 2005.